RISK FACTORS OF PERIODONTAL DISEASE AMONG THE POPULATION - Shirinova, Khilola Khamroqulovna (Educational Research in Universal Sciences, 2023)
This article deals with pathogenesis of periodontitis and metabolic syndrome. Possible mechanisms of connection between diabetes mellitus, arterial hypertension and dyslipidemia and condition of periodontal tissues are analyzed.